Structural confinement-induced highly efficient deep-red emission and negative thermal quenching performance in Mn4+-activated Ca7Mg2Ga6−yAlyO18:Mn4+ phosphors. Issue 9 (14th April 2023) - Huang, Jinmei; Jiang, Pengfei; Cheng, Zien; Wang, Rong; Cong, Rihong; Yang, Tao
Abstract : Extraordinarily high quantum efficiency and abnormal negative thermal quenching were simultaneously achieved in oxide phosphors Ca7 Mg2 Ga6− y Al y O18 :Mn 4+ by structurally confining Mn 4+ -emitters at isolated octahedral sites. Abstract : High quantum efficiency (QE) and thermally stable emission are indispensable for the application of phosphors. Owing to the strong coupling between the lattice and naked d-orbitals of Mn 4+, Mn 4+ -activated oxide red-emitting phosphors usually exhibit a low QE and serious thermal quenching (TQ), which strictly inhibit their prospective application. Herein, we rationally designed a novel phosphor series Ca7 Mg2 Ga6− y Al y O18 :0.02Mn 4+ (CMGA y O:Mn 4+, 0 ≤ y ≤ 1.5), which adopts a high structural symmetry of the space group F 432. Highly efficient and thermally stable deep-red emissions ( λ em = 721 nm) were achieved simultaneously by structurally confining the Mn 4+ -emitting centres at the isolated octahedrally coordinated sites. Specifically, the highest internal and external quantum efficiencies of 90.2 and 75.9%, respectively, were obtained for CMGA1.5 O:Mn 4+ due to Al 3+ -alloying-induced local structure modification and suppression of non-radiative transitions. Excellent thermal stabilities of 99, 102.2, and 87.9% of room-temperature photoluminescence intensities were retained at 423 K for CMGA y O:Mn 4+ with y = 0, 0.5, and 1.5, respectively. CMGA0.5 O:Mn 4+ exhibits an abnormal negative TQ behaviour over the measured temperature range (298–473 K), which is attributed to the energy gain via the electron–phonon interactions of the isolated MnO6 octahedra. Moreover, in situ high-pressure emission spectra of CMGO:0.02Mn 4+ showed that the emission position is highly sensitive to the external pressure with redshift coefficients of 2.8(2) and 1.16(4) nm GPa −1 in different pressure regions. These excellent photoluminescence properties of CMGA y O:Mn 4+ phosphors signify their great application potential in red LEDs and optical pressure sensors. The findings of this work have paved an avenue for the design of high-performance Mn 4+ -activated phosphors.